Effect of Computer Simulation Instructional Strategy on Students’ Attitude and Academic Achievement in Genetics - Akhigbe, Jeremiah Nosakhare; Ogufere, Joy Aghogho (NIU Journal of Social Sciences, 2020)
Concepts in genetics have been perceived to be very difficult by Nigerian students in recent times. This study therefore investigated the effect of computer simulation instructional strategy on senior secondary students’ attitude and achievement in genetics. This was coupled with the moderating effects of gender and ability levels. The design of the study was quasi experimental, while 209 students drawn from four intact classes using purposive sampling techniques constituted the sample size. Six research questions guided the study and emerging hypotheses were tested at .05 level of significance. Quantitative data were collected using questionnaires and achievement tests. The results revealed that the use of computer simulation as a pedagogical tool significantly improve the achievement of students and bolsters their attitude towards biology. Similarly, findings revealed that the instructional use of computer simulation significantly improve the achievement of low ability learners who recorded higher mean gains than the medium and high ability groups respectively. Gendered difference in attitude and achievement did not yield any significant result thereby implying that the instructional use of computer simulations bridges the gap in attitude and achievement of male and female students respectively. The educational implications of these findings were extensively discussed. Keywords: Computer Simulation, Science Attitude, Achievement, Ability Level and Genetics Concepts.